Global trends and future directions of anxiety in adolescent pregnancy: A bibliometric analysis - Dwihestie Luluk Khusnul; Ningrum Allania Hanung Putri Sekar; Agustin Kurnia (BIO Web of Conferences)
Adolescent pregnancy is a global problem today. This problem is higher in developing countries. This causes anxiety in 16%44% of pregnant adolescents. Although not many lead to suicide, the anxiety of pregnant women can lead to poor pregnancy outcomes. This study aims to analyze mental health in adolescent pregnancy. This study used the PRISMA method to search for appropriate keywords in SCOPUS and then conducted a bibliometric analysis to examine the information in scientific publications and literature. The results of this study obtained information that the risk of anxiety disorders increases in teenage pregnant women due to hormonal imbalances in adolescents, unpreparedness in facing pregnancy, and premarital sexual behavior. To prevent anxiety in teenage pregnancy, it is necessary to conduct integrated antenatal care, including mental health screening. Efforts to improve the health of pregnant adolescent mothers can be made by identifying the adaptation process of adolescents regarding changes in roles and responsibilities, increasing the availability of youth-friendly services integrated antenatal care and primary health services, overcoming economic challenges, strengthening the social system of adolescents to undergo pregnancy and parenting.